Varieties of Medical Treatment and Hierarchies of Resort in Johan Turi’s Sámi deavsttat - DuBois, Thomas A. (Umeå University Library, 2010)
Johan Turi’s Sámi deavsttat/Lappish Texts (1918–1919) is examined as a source of information regarding early twentieth-century Sami healing methods and hierarchies of medical resort. Turi’s account of traditional and personal healing experiences in the Čohkkeras/Jukkasjärvi district reflects complex processes of intercultural exchange and hybridization, in which Sami families availed themselves of differing varieties of therapy depending on differing situations and personalities. Hierarchies of resort—that is, the order in which patients make use of competing healing resources—are illustrated by short histories (case studies) which Turi included in the final portion of his work. The text reveals a world in which local Sami noaidevuohta (shamanic healing) lingered as a largely stigmatized clandestine resource, competing variously with shamanic healing offered by more distant (Norwegian) Sami, as well as healing drawn from Finnish magic, Swedish medicine, and Læstadian faith healing. Ill health, insanity, and decimation of one’s herd are depicted as attacks not only on an individual, but on the individual’s entire family, and their effects can be felt ultimately by members of the family’s subsequent generation(s). Non-Sami individuals play important roles both as threats and as sources of potential assistance in the struggle to maintain or regain health.